Technical indicators registered as a function of the playing time in Brazilian basketball - Sato dos Santos, Y. Y.; Monezi, L. A.; Shoiti Misuta, M.; Allegretti Mercadante, L. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
Basketball performance analysis using technical indicators dissociated from the moment they occurred in the game seems to no longer respond to emerging issues of the game as it does not identify the periods when a team`s offensive efficiency has increased or decreased. The aim was to characterize and compare the technical indicators in the positive and negative periods and in the whole game of winning and losing teams in men`s professional basketball. Fourteen games of professional men`s teams of the "Novo Basquete Brasil" Championship in the regular 2011/2012 season were filmed and analyzed. The Kolmogorov-Smirnov test was used to verify data normality. The independent T test was used for variables with normal distribution and the Mann-Whitney test for variables that did not present normal distribution, in order to compare teams` performance. Analysis in the whole game showed that winning teams had significantly higher averages in successful 3-point field goals but in the positive periods, they showed higher averages for successful free throws, successful layups, defensive rebounds and defensive fouls, and in negative periods, losing teams made more defensive and offensive fouls. The teams` performance in the whole game may not elucidate the determinant indicators for building the difference in the scoreboard. It is suggested that coaches should identify the periods of best and worst teams` performance in the game and the indicators involved, preparing teams to overcome the negative periods and obtain more positive periods in the game.